Black corn (Zea mays L.) soluble extract showed anti-inflammatory effects and improved the intestinal barrier integrity in vivo (Gallus gallus). (July 2022) - Agrizzi Verediano, Thaisa; Stampini Duarte Martino, Hércia; Kolba, Nikolai; Fu, Yimin; Cristina Dias Paes, Maria; Tako, Elad
Graphical abstract: Highlights: Black corn soluble extract (BCSE) as a source of anthocyanin improved the intestinal barrier through an intra-amniotic administration in vivo ( Gallus gallus ); The BCSE showed an anti-inflammatory effect through the NF-κB pathway thus, downregulating pro-inflammatory cytokines (TNF-α and IL6); The BCSE intra-amniotic administration improved the intestinal mucus layer by increasing the paneth and goblet cells number; Although the BCSE did not change the tight junction expression, it showed potential to improve the epithelial physical barrier through upregulation of AMPK and CDX2, biomarkers of intestinal barrier integrity; BCSE anthocyanin increased the abundance of E Coli and Clostridium genus, which might have promoted the increase of hepatic glycogen. Abstract: Black corn ( Zea mays L .) is a pigmented type of this cereal whose color of the kernels is attributed to the presence of the anthocyanins. In this study, we assessed the black corn soluble extract (BCSE) effects on the intestinal functionality, morphology, and microbiota composition using an in vivo model ( Gallus gallus ) by an intra-amniotic administration. The eggs were divided into four groups ( n = 6–10): (1) No Injection; (2) 18 MΩ H2 O/cm; (3) 5% (5 mg/mL) BCSE; (4) 15% (15 mg/mL) BCSE. The BCSE showed anti-inflammatory effects by down regulating the gene expression of tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL6), and the transcriptional nuclear factor kappa beta (NF-κB). Further, the BCSE increased the relative abundance of E. coli and Clostridium . 5% and 15% BCSE increased the hepatic glycogen and upregulated the gene expression of sodium-glucose transport protein (SGLT1). In the morphology, 5% and 15% BCSE increased the goblet cell (GC) number on the crypt, the GC size on the villi, Paneth cell number on the crypt, and the acid GC. Further, the BCSE strengthened the epithelial physical barrier through upregulating the intestinal biomarkers AMP- activated protein kinase (AMPK) and caudal-related homeobox transcriptional factor 2 (CDX2). The overall result suggests that the BCSE promotes intestinal anti-inflammatory effects as well as enhances the intestinal barrier function.